(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article describes scientific views on the essence of the concept of inclusive education, numerous pressing problems in the field of inclusive education, social, legal and educational changes that occurred at different stages of the development of society, several principles of inclusive education and the creation of opportunities favorable to ensure full-fledged participation in the educational process, the Universal Declaration of human rights.